2021
DOI: 10.33448/rsd-v10i8.17617
|View full text |Cite
|
Sign up to set email alerts
|

Escala de Usabilidade do Sistema Baseada na Lógica Paraconsistente Anotada Evidencial ET

Abstract: A opinião da experiência do usuário utilizando um software afeta diretamente a qualidade dele. A Escala de Usabilidade do Sistema mensura a experiência do usuário final com o sistema, que apresenta questões que se contradizem. O objetivo deste artigo é demonstrar um aprofundamento das contradições, aplicando a Lógica Paraconsistente Anotada Evidencial Eτ, com a realização de uma pesquisa com onze profissionais que avaliaram um sistema. Foi realizada uma comparação dos resultados da escala SUS com o algoritmo P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…At this point, the Paraconsistent Annotated Evidential Logic Eτ (PAEL; Da Costa, 1999) is an alternative approach to help decision-making based on expert opinion, supporting the acceptance or rejection of the established H0 hypothesis. The paraconsistent logic Et has been used in many different fields, such as engineering, to verify whether the global initiative report's indicators are related to the strong sustainability concept (Langa et al, 2021), in the health areas to illustrate how a reusable multi-criteria decision analysis framework based on paraconsistent theory could be used to aggregate expert perspectives when valuing cancer treatments (Campolina et al, 2022) and, to aid decision-makers in the planning process to solve problems related to the Elective Orthopedic Surgery Agenda, regarding to cancellation or even lack of instruments and consigned material (Duarte et al, 2022), in agriculture to support the developing of a software that predicts stress in the piglet using the vocal calls and committed during stressful conditions (Da Silva et al, 2019), and in the business area to develop and evaluate an instrument's reliability for assessing behavioral competencies for hiring project managers, minimizing subjective bias and possible conflicts of evaluators in the selection process (Do Nascimento et al, 2021) and to evaluate the usability of a software in conjunction with the Para-analyzer, enabling a more detailed analysis (Forçan et al, 2021). In all these studies, the PAEL showed to be an appropriate tool for quantifying subjective opinions and data to sustain a decision.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, the Paraconsistent Annotated Evidential Logic Eτ (PAEL; Da Costa, 1999) is an alternative approach to help decision-making based on expert opinion, supporting the acceptance or rejection of the established H0 hypothesis. The paraconsistent logic Et has been used in many different fields, such as engineering, to verify whether the global initiative report's indicators are related to the strong sustainability concept (Langa et al, 2021), in the health areas to illustrate how a reusable multi-criteria decision analysis framework based on paraconsistent theory could be used to aggregate expert perspectives when valuing cancer treatments (Campolina et al, 2022) and, to aid decision-makers in the planning process to solve problems related to the Elective Orthopedic Surgery Agenda, regarding to cancellation or even lack of instruments and consigned material (Duarte et al, 2022), in agriculture to support the developing of a software that predicts stress in the piglet using the vocal calls and committed during stressful conditions (Da Silva et al, 2019), and in the business area to develop and evaluate an instrument's reliability for assessing behavioral competencies for hiring project managers, minimizing subjective bias and possible conflicts of evaluators in the selection process (Do Nascimento et al, 2021) and to evaluate the usability of a software in conjunction with the Para-analyzer, enabling a more detailed analysis (Forçan et al, 2021). In all these studies, the PAEL showed to be an appropriate tool for quantifying subjective opinions and data to sustain a decision.…”
Section: Introductionmentioning
confidence: 99%